2023
DOI: 10.3390/biomedicines11030724
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Ectopeptidase APN/CD13 in Cancer

Abstract: APN/CD13 is expressed in a variety of cells/tissues and is therefore associated with diverse physiological functions, including proliferation, differentiation, migration, angiogenesis, invasion, metastasis, vasoconstriction, and the regulation of normal and impaired immune function. Increased expression or activity of APN/CD13 has been described for various tumors, such that APN/CD13 is in most cases associated with reduced disease-free and overall survival. The mechanisms that mediate these cellular effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 153 publications
0
3
0
Order By: Relevance
“…However, this may also be attributed to indirect signaling effects. It is important to note that the CD13 inhibitor used in this study is not entirely selective and inhibits other proteases ( Lendeckel et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this may also be attributed to indirect signaling effects. It is important to note that the CD13 inhibitor used in this study is not entirely selective and inhibits other proteases ( Lendeckel et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this may Frontiers in Cell and Developmental Biology frontiersin.org also be attributed to indirect signaling effects. It is important to note that the CD13 inhibitor used in this study is not entirely selective and inhibits other proteases (Lendeckel et al, 2023). Ataxia telangiectasia patients, along with more classical traits, have vasculature abnormalities (Meshulam et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A high level of receptor expression was found in a broad range of cancers, such as breast, prostate, ovarian, thyroid, pancreatic, colorectal, non-small cell lung cancer, and malignant pleural mesothelioma [ 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Although prior literature data state that APN/CD13 cannot be encountered on the surface of normal vasculature [ 9 , 20 ], Curnis et al reported the existence of different isoforms of CD13 in healthy epithelial cells as well as normal blood vessel endothelium and cancer-linked newly formed vasculature [ 21 ].…”
Section: Introductionmentioning
confidence: 99%